2022
DOI: 10.3389/fneur.2022.1009574
|View full text |Cite
|
Sign up to set email alerts
|

Who's driving? The default mode network in healthy elderly individuals at risk of cognitive decline

Abstract: IntroductionAge is the main risk factor for the development of neurocognitive disorders, with Alzheimer's disease being the most common. Its physiopathological features may develop decades before the onset of clinical symptoms. Quantitative electroencephalography (qEEG) is a promising and cost-effective tool for the prediction of cognitive decline in healthy older individuals that exhibit an excess of theta activity. The aim of the present study was to evaluate the feasibility of brain connectivity variable re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 108 publications
0
2
0
Order By: Relevance
“…The processing done with our HCP-compatible pipeline and the source spectra with the BC-VARETA Toolbox of EEG data from the CHBM dataset (Valdes-Sosa et al, 2021) The forward model and source spectra obtained by our structural HCP-compatible pipeline and BC-VARETA Toolbox, respectively, from the EEG of 70 subjects from the Cuban Human Brain Mapping project and the MEG of 70 subjects from the Human Connectome Project were used to perform a statistical comparison between the sources of EEG and MEG rhythms (Riaz et al, 2020) Our BC-VARETA Toolbox was used to analyze the EEG source activity and functional connectivity to explore the feasibility of functional connectivity under aggravating conditions for the spatial resolution of EEG source analysis commonly found in clinical settings. This study (González-López et al, 2022) uses EEGs with a limited number of channels (19 channels) to obtain the inverse problem solution. This proves that BC-VARETA Toolbox is feasible and can be used in clinical settings since it involves significantly lower costs than other neuroimaging tools and can be employed using standard 19-leads EEG to assess brain connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…The processing done with our HCP-compatible pipeline and the source spectra with the BC-VARETA Toolbox of EEG data from the CHBM dataset (Valdes-Sosa et al, 2021) The forward model and source spectra obtained by our structural HCP-compatible pipeline and BC-VARETA Toolbox, respectively, from the EEG of 70 subjects from the Cuban Human Brain Mapping project and the MEG of 70 subjects from the Human Connectome Project were used to perform a statistical comparison between the sources of EEG and MEG rhythms (Riaz et al, 2020) Our BC-VARETA Toolbox was used to analyze the EEG source activity and functional connectivity to explore the feasibility of functional connectivity under aggravating conditions for the spatial resolution of EEG source analysis commonly found in clinical settings. This study (González-López et al, 2022) uses EEGs with a limited number of channels (19 channels) to obtain the inverse problem solution. This proves that BC-VARETA Toolbox is feasible and can be used in clinical settings since it involves significantly lower costs than other neuroimaging tools and can be employed using standard 19-leads EEG to assess brain connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Another CiftiStorm application was the study of spectral source connectivity measures derived from the SSSBL method applied to individuals at risk of cognitive decline (González-López et al, 2022). This study reported meaningful and statistically significant source connectivity changes even when SSSBL was used to obtain inverse solutions from a 10-20 EEG system (19 sensors) commonly found in clinical settings.…”
Section: Comparing Eeg/meg Inverse Solutionsmentioning
confidence: 97%